Socioeconomic determinants of cervical cancer screening in Latin America - Soneji, Samir (2013)
OBJECTIVE: To assess the impact of health care access and socioeconomic determinants on Pap smear screening in Latin America. METHODS: Individual-level data was collected from the Demographic and Health Surveys in Bolivia, Brazil, Dominican Republic, Ecuador, Guatemala, Nicaragua, Peru, and Trinidad and Tobago between 1987 and 2008. Multivariate logistic regression analyses were used to identify socioeconomic and health care determinants of two outcomes: knowledge of Pap smears and recent Pap smear screening. RESULTS: In all countries, the proportion of women with a recent Pap smear screening remained below 55%. Key determinants of knowledge of Pap smears were age, education, and recent doctor’s visit. For recent Pap smear screening, key determinants were wealth and recent doctor’s visit. Women were between 1.47 and 3.44 times more likely to have received a recent Pap smear if they had a recent doctor’s visit. Even the poorest women with a recent doctor’s visit were more likely to screen than the richest women without a recent visit. CONCLUSIONS: These data suggest that visiting a doctor is an important determinant of cervical cancer screening in Latin America. Because screening may coincide with other medical visits, physicians could effectively encourage screening.